Model Pembelajaran Berbasis Alam untuk Meningkatkan Ecoliterasi Anak Usia Dini - Nopiana Nopiana (Journal of Humanities, Social Sciences, and Education, 2025)
Ecoliteracy or ecological intelligence is an important competency that needs to be developed from an early age in order to form a generation that cares and is responsible for the environment. Early Childhood Education (PAUD) has a strategic role in instilling ecological values ​​through a learning approach that is in accordance with the characteristics of children, namely active, concrete, and explorative. The nature-based learning model is an approach that is considered effective because it involves children directly with the natural environment through the experience of playing, observing, and exploring nature. This literature study aims to examine the effectiveness of the nature-based learning model in improving early childhood ecoliteracy. This study uses a qualitative approach through a literature review of various relevant national and international journals in the last five years. The results of the study show that the nature-based learning model is able to improve children's understanding of environmental concepts, foster a love of nature, improve observation and exploration skills, and form environmentally friendly behavior from an early age. Nature-based learning also encourages collaboration between educators, families, and communities in supporting ecologically sustainable child growth and development. The implications of this study indicate that the integration of the nature approach in the PAUD curriculum needs to be designed systematically in order to be able to strengthen children's ecoliteracy holistically